2016
DOI: 10.1371/journal.pone.0153416
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Reaction Vessels Designed for Synthesis of Copper-Drug Complexes Suitable for Preclinical Development

Abstract: The development of copper-drug complexes (CDCs) is hindered due to their very poor aqueous solubility. Diethyldithiocarbamate (DDC) is the primary metabolite of disulfiram, an approved drug for alcoholism that is being repurposed for cancer. The anticancer activity of DDC is dependent on complexation with copper to form copper bis-diethyldithiocarbamate (Cu(DDC)2), a highly insoluble complex that has not been possible to develop for indications requiring parenteral administration. We have resolved this issue b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 41 publications
2
61
0
1
Order By: Relevance
“…We have previously described a method that solves the formulation issue: a method wherein the copper-complexation reaction occurs inside copper-containing liposomes. 19 Here we demonstrate, for the first time, the anticancer activity of the resultant Cu(DDC) 2 formulation. This method allows for the development of a parenterally suitable Cu(DDC) 2 formulation and can take advantage of the well-established potential for liposomes to modulate the PK characteristics of an associated drug candidate.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…We have previously described a method that solves the formulation issue: a method wherein the copper-complexation reaction occurs inside copper-containing liposomes. 19 Here we demonstrate, for the first time, the anticancer activity of the resultant Cu(DDC) 2 formulation. This method allows for the development of a parenterally suitable Cu(DDC) 2 formulation and can take advantage of the well-established potential for liposomes to modulate the PK characteristics of an associated drug candidate.…”
Section: Introductionmentioning
confidence: 79%
“…13,35,36 We, as well as others, have previously shown that the cytotoxicity of DSF and Cu is attributed to the formation of a Cu(DDC) 2 complex. 11,19 Attempts have been made to prepare the complex in vivo by administering DSF and Cu (usually given as Cu-gluconate) separately. However, the PK and distribution behaviors of copper and DSF are remarkably different and this has contributed to the lack of success using this approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations